Lived Religion in the Ancient Mediterranean World Approaching Religious Transformations from Archaeology, History and Classics - Gasparini, Valentino; Patzelt, Maik; Raja, Rubina (De Gruyter, 2020)
The Lived Ancient Religion project has radically changed perspectives on ancient religions and their supposedly personal or public character. This volume applies and further develops these methodological tools, new perspectives and new questions. The religious transformations of the Roman Imperial period appear in new light and more nuances by comparative confrontation and the integration of many disciplines. The contributions are written by specialists from a variety of disciplinary contexts (Jewish Studies, Theology, Classics, Early Christian Studies) dealing with the history of religion of the Mediterranean, West-Asian, and European area from the (late) Hellenistic period to the (early) Middle Ages and shaped by their intensive exchange. From the point of view of their respective fields of research, the contributors engage with discourses on agency, embodiment, appropriation and experience. They present innovative research in four fields also of theoretical debate, which are "Experiencing the Religious", "Switching the Code", "A Thing Called Body" and "Commemorating the Moment".